Dampak depresiasi rupiah terhadap perekonomian jangka panjang - Sri Adiningsih (Universitas Islam Indonesia, 1997)
Since July, 1997, a crisis in currency markets has been running into Asian countries. These countries which were known as high performance Asian economic countries (HPAEs) were suddenly knocked down by a prolonged crisis.